DNA Profiling, Bioinformatics and Databases in Forensics: Human Identification Purposes - Meilana, Andi Nur Sakina Tri; Auerkari, Elza Ibrahim (Newinera Publisher, 2024)
Individual identification is an essential element in establishing truth the forensic investigation process, be it in criminal, medico-legal, or mass disasters case. When ante-mortem data are not available, the only thing that can be used is identification trough DNA. Alec Jeffrey, a geneticist (1984), found that certain regions of DNA contain repetitive sequences and the number of repetitions in individuals differs from one another. This identification method known as DNA profiling. DNA profiling is described as an important and significant discovery in forensics and has been considered as the standard in modern human identification. Until now, the recommended DNA profiling method must be based on the PCR to analyze degraded DNA and short-sized DNA (Short Tandem Repeats) through PCR amplification. In profiling, the result DNA amplification are analyzed through genetic markers (DNA Markers) and then matched into the database or compared with the collected reference samples. In the human genome, the genetic markers most frequently used in forensics are autosomal STR, Y-STR, mtDNA, X-STR, SNPs, and Amelogenin. Accomplishment of proving the suitability of DNA profiles, an application of bioinformatics in forensics is carried out. Bioinformatics is a combination of molecular biology and computer informatics that aims to manage and analyze data and store biological (genetic) information. DNA database is an application of bioinformatics in the form of special software which has become an important tool for biologists and forensics. This genetic database will predict the similarities between one DNA profile and another.